2018
DOI: 10.3390/en11020388
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Structural Characteristics of Microalgal Cells Walls under the Influence of Turbulent Mixing Energy in Open Raceway Ponds

Abstract: Turbulent flow mixing is essential in optimizing microalgal cultivation in raceway ponds. Microalgal cells are however highly sensitive to hydrodynamic stresses produced by turbulent mixing because of their small size. The mechanical properties (wall deformation and von Misses stress) of the microalgal cell wall structure under the influence of turbulent mixing are yet to be explored. High turbulence magnitudes damage microalgal cell walls by adversely affecting their mechanical properties which consequently d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Measurements were used in this study to examine the microalgal mixing processes due to turbulent coherent structures. To date, extensive investigation has been conducted to link turbulent coherent structures to describe the near-bed non-organic material resuspension process [21,23,49]; however, no one investigated the organic material mixing…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Measurements were used in this study to examine the microalgal mixing processes due to turbulent coherent structures. To date, extensive investigation has been conducted to link turbulent coherent structures to describe the near-bed non-organic material resuspension process [21,23,49]; however, no one investigated the organic material mixing…”
Section: Discussionmentioning
confidence: 99%
“…Measurements were used in this study to examine the microalgal mixing processes due to turbulent coherent structures. To date, extensive investigation has been conducted to link turbulent coherent structures to describe the near-bed non-organic material resuspension process [21,23,49]; however, no one investigated the organic material mixing mechanism (microalgae in our case) in such detail towards the development of a precise 'microalgae mixing model' merging turbulence features. Two contrasting race ponds, one powered by a paddlewheel and the other by jet, were inspected in order to look at the mechanisms involved in the mixing process of microalgae, where it has been observed that turbulent bursting events have a significant contribution towards microalgal mixing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study used a large-scale 3D raceway pond with a length (L) of 23 m and a channel width (W) of 2.25 m (Figure 1a). The 2D paddle wheel comprises six blades (0.55 m × 0.04 m) with a diameter of 0.6 m. The boundary-connected coupling technique was applied to import the flow effects of the 2D paddle wheel in the 3D raceway pond [24][25][26][27][28]. The Reynolds number (Re) based on hydraulic diameter (D h ) was utilized to characterize the flow in the raceway pond.…”
Section: Raceway Pondmentioning
confidence: 99%
“…The transport of diluted species interface of COMSOL-Multiphysics was utilized to simulate the concentration of nutrients in the raceway pond. A 2D paddle wheel was modeled and coupled with the 3D raceway pond using the boundary-connected coupling methodology to save the computational memory and time [24][25][26][27][28]. The 2D paddle wheel was simulated with the rotating machinery interface of the COMSOL-Multiphysics.…”
Section: Numerical Simulation and Mesh Generationmentioning
confidence: 99%